2016
DOI: 10.1111/1752-1688.12471
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effects of Tile Drain Placement on the Hydrologic Function of Farmed Prairie Wetlands

Abstract: The early 2000s saw large increases in agricultural tile drainage in the eastern Dakotas of North America. Agricultural practices that drain wetlands directly are sometimes limited by wetland protection programs. Little is known about the impacts of tile drainage beyond the delineated boundaries of wetlands in upland catchments that may be in agricultural production. A series of experiments were conducted using the well‐published model WETLANDSCAPE that revealed the potential for wetlands to have significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…Thus, shallower systems would have greater potential to affect wetland hydrology when solely relying on the setback distance to limit such effects. Werner et al (2016) concluded that changes to wetland period of inundation in a low-relief terrain were more sensitive to the depth of an SDS than to the distance (i.e., setback) from a wetland, substantiating the importance of considering SDS characteristics such as depth when assessing potential effects to wetland hydrology.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Thus, shallower systems would have greater potential to affect wetland hydrology when solely relying on the setback distance to limit such effects. Werner et al (2016) concluded that changes to wetland period of inundation in a low-relief terrain were more sensitive to the depth of an SDS than to the distance (i.e., setback) from a wetland, substantiating the importance of considering SDS characteristics such as depth when assessing potential effects to wetland hydrology.…”
Section: Discussionmentioning
confidence: 92%
“…Subsurface drainage systems (SDSs) are used throughout the United States to enhance agricultural production by facilitating water management. Historically, use of SDSs has been prevalent in the southeastern portions of the PPR (Iowa, Minnesota); however, use of these systems expanded rapidly into North Dakota and South Dakota (hereafter, Dakotas) during the 2000s in response to rising commodity prices, most notably corn, which peaked around 2012 (Roth and Capel 2012;Johnston 2013;Finocchiaro 2016;Werner et al 2016). Subsurface drainage systems typically consist of perforated drainage pipe placed in various configurations below the soil surface to target specific areas (e.g., wetlands) or manage the water table of entire fields.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations